Utilization and outcomes of polytetrafluoroethylene covered stents in patients with coronary artery perforation and coronary artery aneurysm: Single center 15‐year experience. Issue 4 (20th August 2019) - Parikh, Parth; Banerjee, Kinjal; Sammour, Yasser; Ali, Ambreen F.; Sankaramangalam, Kesavan; Nair, Ravi; Ellis, Stephen; Raymond, Russell; Tuzcu, E. Murat; Kapadia, Samir
Abstract: Objectives: Determine the outcomes of polytetrafluoroethylene (PTFE) covered stents for coronary artery perforation (CAP) and coronary artery aneurysm (CAA). Background: PTFE covered stents have been used for treatment of potentially life‐threatening CAP and CAA. The short and long‐term outcomes of the PTFE covered stent for CAP and CAA have not been well studied. Methods: We performed a retrospective study of PTFE covered stents that were placed in the patients from 2003 to 2017. Short term outcomes included in‐hospital mortality, pericardial effusion, cardiac tamponade, and length of stay. Long‐term outcomes included target lesion revascularization (TLR), in‐stent restenosis (ISR), and long‐term mortality. Results: Fifty‐three PTFE covered stents were placed in 32 patients of which there were 24 patients with a CAP with a mean age of 75 ± 8 years. Two patients died in‐hospital, with no additional deaths at 30 days. The rate of ISR was 25%, with estimated rates of TLR of 2.6% (3 years) and 17.8% (5 years). The median survival was 55.6 months, with survival at 10 years estimated to be 30.9%. Eight patients received a PTFE covered stent for CAA with a mean age of 59 ± 15 years with no in‐hospital or 30‐day mortality. Median follow‐up of 49 months showed no evidence of TLR. The all‐cause mortality was 12% at 1 year and 38% at 3 years. Conclusions: PTFE covered stents is an effective option in patients with CAP and CAA. The long‐term outcomes may be related to the pathology of the disease rather than the stent itself.